Beta-blocker use and urothelial bladder cancer survival: a Swedish register-based cohort study. (3rd August 2022) - Udumyan, Ruzan; Botteri, Edoardo; Jerlstrom, Tomas; Montgomery, Scott; Smedby, Karin E.; Fall, Katja
Abstract: Background: Recent observational studies linked β-adrenergic receptor blocker use with improved survival in patients with several cancer types, but there is no information on the potential effects of β-blockers in patients with bladder cancer. Literature from pre-clinical studies is also limited, but urothelial cancer can exhibit significant overexpression of β-adrenergic receptors relative to normal urothelial tissue, suggesting that urothelial cancer may benefit from β-blockade therapy. We thus aimed to explore the possible association between β-blocker use and bladder cancer-specific mortality (BCSM) among patients with urothelial bladder cancer. Material and methods: Patients diagnosed during 2006–2014 and identified from the Swedish Cancer Register ( n = 16, 669) were followed until 31 December 2015. Cox regression was used to evaluate the association of β-blockers dispensed within 90 days prior to cancer diagnosis with BCSM (primary outcome) and all-cause mortality, while controlling for socio-demographic factors, tumor characteristics, comorbidity, other medications and surgical procedures. Hazard ratios (HR) with 95% confidence intervals (CI) were reported. Results: Overall, β-blocker use was associated with lower BCSM [HR 0.88 (95%CI 0.81–0.96)]. Especially use of nonselective β-blockers showed a clear inverse association in comparison with both nonuse [0.66 (0.50–0.86)] and use of other antihypertensive medications [0.72 (0.54–0.95)]. The inverse association was most pronounced among patients with locally advanced/metastatic disease: [0.35 (0.18–0.68)]. A lower-magnitude inverse association was observed for selective β-blocker use [0.91 (0.83–0.99)]. Largely similar inverse associations were observed for hydrophilic [0.82 (0.70–0.95)] and lipophilic [0.91 (0.83–1.00)] β-blocker use. Conclusion: β-blocker use, particularly of the nonselective type, was associated with lower BCSM, especially in patients with locally advanced/metastatic urothelial bladder cancer.